2022
DOI: 10.1101/2022.06.24.22276885
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serological and Molecular Study on Caprine Brucellosis in Puducherry (India) and its Public Health Significance

Abstract: Caprine brucellosis due to Brucella melitensis is an important zoonotic disease. The present study was carried out to address the lack of a comprehensive study on the status of caprine brucellosis in Puducherry, India using serological and molecular tests in goats and to assess the seroprevalence in human risk groups of the aforementioned region to ascertain the public health significance of the disease. Seroprevalence in 120 goats was found to be zero, 3.33% and 18.33% by Rose Bengal agglutination Test (RBT),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
1
1
Order By: Relevance
“…Some previous studies have reported an apparently lower prevalence of brucellosis in small ruminants of different parts of the world, such as 0.99% in the western borders of Pakistan [ 8 ], 6.6% in Kampala, Uganda [ 19 ], 5.59% in Tamil Nadu, India [ 20 ], and 5.8% in Kurdistan, Western Iran [ 21 ]. In contrast to current findings, some previous studies also reported a higher prevalence of brucellosis in small ruminants, such as 12.29% in district Kasur and Sheikhupura, Pakistan [ 15 ], 15.5% in goat and 8.6% in sheep populations of Baringo County, Kenya [ 22 ], 18.3% in Puducherry, India [ 10 ], 18.5% in Tarbiz, Iran [ 23 ], and 31.25% in goat and 22.5% in sheep populations of Matrouh governorate, Egypt [ 9 ]. The difference in values might be due to differences in diagnostic techniques, agroecological zones, geoclimatic conditions, husbandry practices, and traditions and culture [ 24 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Some previous studies have reported an apparently lower prevalence of brucellosis in small ruminants of different parts of the world, such as 0.99% in the western borders of Pakistan [ 8 ], 6.6% in Kampala, Uganda [ 19 ], 5.59% in Tamil Nadu, India [ 20 ], and 5.8% in Kurdistan, Western Iran [ 21 ]. In contrast to current findings, some previous studies also reported a higher prevalence of brucellosis in small ruminants, such as 12.29% in district Kasur and Sheikhupura, Pakistan [ 15 ], 15.5% in goat and 8.6% in sheep populations of Baringo County, Kenya [ 22 ], 18.3% in Puducherry, India [ 10 ], 18.5% in Tarbiz, Iran [ 23 ], and 31.25% in goat and 22.5% in sheep populations of Matrouh governorate, Egypt [ 9 ]. The difference in values might be due to differences in diagnostic techniques, agroecological zones, geoclimatic conditions, husbandry practices, and traditions and culture [ 24 ].…”
Section: Discussioncontrasting
confidence: 99%
“…A single infected male can sexually transmit the disease to several females [ 7 ]. A considerable variation in the prevalence of brucellosis (ranging from 1%–32%) has been reported in small ruminant populations of different parts of the world [ 8 10 ], and various socio-cultural and management/husbandry practices have been reported to contribute to this varying prevalence in small ruminants [ 4 ]. Control of brucellosis largely depends on intensive screening and surveillance of the illness, both in animals and humans.…”
Section: Introductionmentioning
confidence: 99%